A new environmental public health practice to manage current and future global health challenges through education, training, and capacity building - Leonardi, Giovanni S.; Zeka, Ariana; Ashworth, Matthew; Bouland, Catherine; Crabbe, Helen; Duarte-Davidson, Raquel; Etzel, Ruth Ann; Giuashvili, Nia; Gökdemir, Özden; Hanke, Wojciech; van den Hazel, Peter; Jagals, Paul; et al. (Frontiers in Public Health, 2024)
Unsustainable globalisation of economic activities, lifestyles and social structures has contributed to environmental degradation, posing major threats to human health at the local and global levels. All these problems including climate change, pollution, and biodiversity loss represent challenges that are unlikely to be met with existing approaches, capabilities and tools. This article acknowledges the need for well-prepared practitioners from many walks of life to contribute to environmental public health (EPH) functions thus strengthening society’s capacity and capability to respond effectively and in a timely manner to such complex situations and multiple challenges. It envisions a new EPH practice addressing questions on: Why do this? What needs to be addressed? Who will do it? How can it be implemented? This article focuses on the main challenging EPH issues worldwide and how they could be addressed using a conceptual framework for training. A companion article shows how they have been tackled in practice, providing ideas and experiences.